Cases review : judges always promote the concept of morality, justice, and equality in every decided case - Nurin Fatehah Hussein,; Nurul Najwa Faris,; Althabhawi, Nabeel Mahdi (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2022)
Reaffirming the Malaysian judiciary’s commitment to uphold the rule of law, it is vitally important for all judges to uphold morality, justice, and equality in deciding on court cases. There is a quote by Chief Justice Tun Tengku Maimun Tuan Mat, where she said that every judge must-have qualities of integrity, competency and efficiency, and be always mindful that they are “not beholden to anybody or anything but the law”. “Without these key qualities, justice would not be truly served, and we would have failed in our duty. From the quote, we can clearly see that judges will decide on court cases based on the law and evidence and will not let fear or favour influence their rulings. However, a number of cases have come to light recently because of judges’ decisions that appear to be unjust. For example, a single mother with nine children sentenced to death for meth possession and a man put to death for murdering a house intruder are two of the most high-profile examples. Arguments over whether judges’ decisions are guided by morality, justice, and equality are common in these cases. The general discussion of the rule of the notion of morality, justice, and equality in resolving every case is the subject of this investigation. In the course of obtaining answers to our inquiries, we select two cases to determine whether the court has adopted and promoted the concepts of justice, equality, and morality before passing judgement. The findings of this article demonstrated that, while persons may have their own reasons for conducting an act, this does not exempt them from the requirement to abide by Malaysian law. When it came to making a decision in a case, judges always incorporated the concepts of morality, justice, and equality.